Integrasi Kecerdasan Digital dan Emosional dalam Kepemimpinan Pendidikan Tinggi: Kajian Sistematik Menuju Universitas 5.0: Integrasi Kecerdasan Digital dan Emosional dalam Kepemimpinan Pendidikan Tinggi: Kajian Sistematik Menuju Universitas 5.0 - Ismail Nasar; I GdeWawan Sudatha; I Kadek Suartama; Made Hery Santosa; Fabianus Bosco (Journal of Innovative and Creativity, 2025)
Digital transformation in higher education necessitates a leadership model that is both responsive to technological advancements and attuned to the emotional dynamics within institutions The study purpose was to investigate the integration of digital leadership and emotional intelligence (EI) in the context of higher education through a Systematic Literature Review (SLR) approach. The study aimed to identify how the synergy between digital competencies and emotional sensitivity can enhance institutional leadership during digital transformation. Materials and methods. The SLR methodology involved a comprehensive search and selection process across major academic databases, applying inclusion criteria focused on relevance, recency, and methodological rigor. Articles were then thematically analyzed to identify recurring patterns and conceptual intersections between digital leadership and emotional intelligence in educational leadership contexts. Results: The analysis revealed four dominant themes: (1) leadership dynamics in the era of university 5.0, (2) the impact of digital leadership on transformation effectiveness, (3) the role of emotional intelligence in educational leadership, and (4) the synergy between digitalization and emotional values. These findings indicate that leadership models combining digital competencies and emotional intelligence enhance institutional collaboration, communication, and readiness for continuous change. Conclusions. Although research integrating digital leadership with emotional intelligence remains limited, current empirical evidence underscores the value of humanistic and adaptive leadership in navigating digital transformation. The study advocates for a comprehensive leadership framework in higher education that balances technological literacy with emotional acuity to foster inclusive, resilient, and sustainable academic institutions